"A great moment . . . because of the music": An exploratory study on music therapy and early interaction with children with visual impairment and their sighted caregivers. (May 2015) - Metell, Maren
The focus of this article is on how musical interaction can contribute to bonding and early interaction. This article is based on a music therapy project in a pedagogical institution for people with visual impairment. The study is qualitative and exploratory, where children with visual impairments (aged 1–4 years) and their caregivers participated in music therapy sessions over 10 weeks. Data have been collected by participant observation, video recordings, and interviews. Moments of positive interactions in music were selected and analyzed, and the selections were triangulated by interviews with the caregivers. The data material indicates that music therapy promotes positive bonding patterns and enhances early interaction. Musical interaction facilitates elements of early interaction that can be challenging for children with visual impairments and their sighted caregivers. Both caregivers and children seemed to experience one another as a source of joyful interaction. This article discusses the findings in the broader perspective of disability studies and community music therapy and argues that music therapy promotes positive interactions and empowerment of children with visual impairment and their caregivers.